2016
DOI: 10.7243/2049-7962-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer or sarcoidosis: A diagnostic dilemma

Abstract: Background: Small cell lung cancer is a neuroendocrine neoplasm representing about 15 percent of all lung cancers. Sarcoidosis is a multisystem granulomatous disease. The involvement of mediastinal lymph nodes is common in both and makes the diagnosis challenging when these conditions coexist. We report a rare case of a patient with history of sarcoidosis who was diagnosed with small cell lung cancer. Case presentation: 65-year-old African American female with history of sarcoidosis, who presented with right s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Prior case reports described the need for a surgical lung biopsy to obtain sufficient tissue for a definitive diagnosis [ 4 , 6 ], which was the case in our patient. However, the presence of granulomas does not necessarily rule out a malignancy, because non-caseating granulomas have been reported in some instances of small cell lung cancer [ 7 ]. Moreover, the presence of non-caseating granulomas in association with a malignancy, described as a sarcoid-like reaction, has been shown to occur adjacent to the site of the malignancy or around local lymph nodes [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior case reports described the need for a surgical lung biopsy to obtain sufficient tissue for a definitive diagnosis [ 4 , 6 ], which was the case in our patient. However, the presence of granulomas does not necessarily rule out a malignancy, because non-caseating granulomas have been reported in some instances of small cell lung cancer [ 7 ]. Moreover, the presence of non-caseating granulomas in association with a malignancy, described as a sarcoid-like reaction, has been shown to occur adjacent to the site of the malignancy or around local lymph nodes [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are closely followed-up with chest X-rays, pulmonary function tests, and clinical evaluation. 3 , 7 , 8 , 15 , 16 Corticosteroid therapy is used in patients who have severe symptoms, hypercalcemia, neurologic or cardiovascular or ocular involvement, and progressive pulmonary disease. If patients have refractory disease not responding to corticosteroids with progression, methotrexate may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Wolbech et al first described sarcoid like reactions in two autopsy cases of carcinoma of colon and jaw [15]. A case of small cell lung cancer in lung nodule with sarcoid like reaction in mediastinal and hilar lymph nodes causing diagnostic dilemma regarding lymph node metastasis has been reported [14]. Tan et al reported a case with lung adenocarcinoma who underwent lobectomy and 4 years later developed new mediastinal and hilar adenopathy that revealed sarcoid like reaction in Endobronchial ultrasound (EBUS) guided fine needle aspiration [10].…”
Section: Discussionmentioning
confidence: 99%
“…Granulomatous inflammation can rarely be seen in lung cancer tumors and regional draining lymph nodes which is called 'sarcoid like reaction' as they do not fulfill the criteria for systemic sarcoidosis [2]. Sarcoid like reaction can coexist with malignancy either at the time of diagnosis or later during follow up after treatment or from oncologic immunotherapy [2,10,14]. It can be challenging at times in such cases when tissue biopsies only pick up sarcoid changes without revealing malignancy because of sampling areas in that particular tumor and further delaying the actual diagnosis which happened in our case.…”
Section: Introductionmentioning
confidence: 99%